REVITALISASI LITERASI KEPEMIMPINAN DALAM MEMBANGUN SDM LEMBAGA DAKWAH YANG UNGGUL DI ERA DISRUPSI - Al Kahfi; Cecep Castrawijaya (UIN Sunan Kalijaga, 2024)
Leadership literacy is a fundamental element in developing excellent human resources (HR) within Islamic preaching institutions, especially in the era of disruption characterized by rapid social, technological, and communication changes. This study employs a literature review method by analyzing books, reputable international journals, and academic documents to understand how leadership literacy is a key strategy in enhancing the effectiveness and efficiency of HR management in Islamic preaching institutions. The findings indicate that leaders with strong leadership literacy can manage organizations adaptively, utilize technology in preaching, and establish sustainable leadership regeneration systems. Moreover, leadership literacy contributes to fostering an innovative organizational culture, strengthening collaborative networks, and improving leadership succession in response to global challenges. Thus, this study emphasizes that revitalizing leadership literacy is crucial for developing excellent human resources within Islamic preaching institutions and ensuring their relevance in the modern era.